#72 Development of novel near-infrared fluorescence probes for earlier diagnosis of AD - Modi, Gyan Prakash; Rai, Himanshu; Singh, Rishabh; Shankar, Gauri; Krishnamurthy, Sairam; Gupta, Sarika; Kumar, Saroj (Journal of Pharmaceutical Chemistry, 2022)
The appearance of Alzheimer’s disease (AD) marker proteins 10-15 years earlier in the asymptomatic period makes them a versatile target for detecting and quantifying AD etiology. We aim to develop novel near-infrared fluorescence (NIRF) imaging agents for the selective detection of the pathological hallmarks of the disease, such as Aβ and tau aggregates. Early detection can help effective AD management and evaluate appropriate therapeutic interventions in preclinical and clinical studies. Advances in microscopic optical imaging techniques, especially with the aid of fluorescence molecular tomographic (FMT) imaging, reveal that fluorescent chemicals that penetrate the blood-brain barrier (BBB) and label AD markers protein with a high specificity could be evolved as a choice of interest in the near future. We designed NIRF probes using a widely preferable donor-π-acceptor (D-π-A) scaffold to develop molecular probes that efficiently penetrate BBB and label AD marker proteins. The design, synthesis, and characterization of the novel probes were carried out using the area of synthetic organic chemistry. The fluorescent properties of the developed imaging agents were calculated to determine solvatochromism and the potential for in-vivo imaging. The cell viability assay of the promising probes indicates their safer profile for in-vivo imaging purposes. Other experimental assessments like a pH stability study for 24 h revealed that these probes retain their fluorescence properties for longer with no significant decay. The lead probes were tested selectively to detect the Aβ and tau aggregates using fluorescence-based assays. The developed probes exhibited the excitation maxima in 480-540 nm and emission maxima in the range of 580 to 750 nm. The in-vitro fluorescence assay revealed that the lead probes also could selective detect Aβ and tau aggregates over BSA. We have identified I3, I8, I16, and I28 as potential leads to further investigation in the transgenic animal and Drosophila model of AD.
Keywords: aaa